PENGEMBANGAN BAHAN AJAR MULTIMEDIA UNTUK PEMBELAJARAN IPA SD - Dhian Dwi Nur Wenda (Universitas PGRI Yogyakarta, 2016)
Based on preliminary study, it was found the problem that teachers often had difficulty to give real picture related to materials which are beyond the observation of students. The limitations of media and learning resources forced teachers to deliver the material with the lecture method. Limited learning sources and use of learning methods that were less appropriate to the characteristics of the students which had an impact on students' lack of interest in material and activities and student learning outcomes became less maximal. The research objective was to produce multimedia teaching materials were valid, practical, attractive, and effective to be used in science learning of elementary school, and test the feasibility of teaching materials products which included validity, practicality, the attractiveness and effectiveness of the product. This study used a model of the development of a modified Borg & Gall. The steps of this research are (1) Preliminary Study, (2) planning, (3) Product Design, (4) Product Validation, (5) Testing Products, and (6) End Products. The level of validity data products were obtained from the result of expert validation which had criteria valid enough. The results of questionnaire practicality material showed that teaching materials had very practical criteria; the results of attractiveness questionnaire indicate the criteria of teaching materials are very attractive, the result of effectiveness questionnaire showed that criteria of materials are effective.